Katalog wymagań wobec współczesnego controllera - Janczyk-Strzała, Elżbieta (Requirements Catalogue for Contemporary Controller, 2005)
This article is dedicated to the significant role of controller in contemporary companies. It de-scribes the qualifications of an effective controller.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 212-217